Jump-Starting Self-Employment? Evidence for Welfare Participants in Argentina - Almeida, Rita K.; Galasso, Emanuela (2012)
We evaluate the effects of a self-employment program offered to welfare beneficiaries of a large safety net program in Argentina. The program promotes self-employment by providing financial and technical assistance. Our findings show that only a small and selected subset of welfare beneficiaries is attracted to this type of exit strategy (female household heads and more educated). Exploring non-experimental methods, we also show that in the short-run participation in the program affects the labor supply of participants, by reducing the probability of having an outside job and increasing the total number of hours worked. However, at least in the short-run, the intervention fails to produce income gains to the average participant.